Immune-Boosting and Antiviral Effects of Antioxidants in COVID-19 Pneumonia: A Therapeutic Perspective - Stefano Sanduzzi Zamparelli; Alessandro Sanduzzi Zamparelli; Marialuisa Bocchino (Life)
The COVID-19 pandemic caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has profoundly impacted global health, with pneumonia emerging as a major complication in severe cases. The pathogenesis of COVID-19 is marked by the overproduction of reactive oxygen species (ROS) and an excessive inflammatory response, resulting in oxidative stress and significant tissue damage, particularly in the respiratory system. Antioxidants have garnered considerable attention for their potential role in managing COVID-19 pneumonia by mitigating oxidative stress and modulating immune responses. This review provides a comprehensive overview of the literature on the use of antioxidants in hospitalized patients with mild-to-moderate COVID-19. Studies exploring antioxidants, including vitamins, trace elements, nitric oxide (NO), ozone (O3), glutathione (GSH), L-carnitine, melatonin, bromelain, N-acetylcysteine (NAC), and numerous polyphenols, have yielded promising outcomes. Through their ROS-scavenging properties, these molecules support endothelial function, reduce the thrombosis risk, and may help mitigate the effects of the cytokine storm, a key contributor to COVID-19 morbidity and mortality. Clinical evidence suggests that antioxidant supplementation may improve patient outcomes by decreasing inflammation, supporting immune cell function, and potentially shortening recovery times. Furthermore, these molecules may mitigate the symptoms of COVID-19 by exerting direct antiviral effects that inhibit the infection process and genomic replication of SARS-CoV-2 in host cells. Moreover, antioxidants may work synergistically with standard antiviral treatments to reduce viral-induced oxidative damage. By integrating findings from the literature with real-world data from our clinical experience, we gain a more profound understanding of the role of antioxidants in managing COVID-19 pneumonia. Further research combining comprehensive literature reviews with real-world data analysis is crucial to validate the efficacy of antioxidants and establish evidence-based guidelines for their use in clinical practice.